Second Periprosthetic Joint Infection Caused by Streptococcus dysgalactiae: How Genomic Sequencing Can Help Defining the Best Therapeutic Strategy - Pham, Truong-Thanh; Lazarevic, Vladimir; Gaia, Nadia; Girard, Myriam; Cherkaoui, Abdessalam; Suva, Domizio; Schrenzel, Jacques (Frontiers in Medicine, 2020)
Primary and revision arthroplasties are increasing worldwide, as are periprosthetic joint infections (PJI). The management of PJI requires surgery, the strategy of which is dictated by the acute or chronic nature of the infection, with an exchange of the implant in the event of a chronic PJI or in the case of recurrence with the same pathogen. We report the case of a 63-year-old man with 2 episodes of Streptococcus dysgalactiae subsp. equisimilis PJI within 9 months. Based on clinical suspicion of an haematogenous PJI, the patient was treated by DAIR (debridement, antibiotics, implant retention), while genomic sequencing revealed 2 different strains, confirming our hypothesis that no additional surgery was needed. Hence, we report a case where genomic analysis was decisive for the decision of the best therapeutic strategy.